2017
DOI: 10.1007/s11356-017-9883-7
|View full text |Cite
|
Sign up to set email alerts
|

Two sampling strategies for an overview of pesticide contamination in an agriculture-extensive headwater stream

Abstract: Two headwaters located in southwest France were monitored for 3 and 2 years (Auvézère and Aixette watershed, respectively) with two sampling strategies: grab and passive sampling with polar organic chemical integrative sampler (POCIS). These watersheds are rural and characterized by agricultural areas with similar breeding practices, except that the Auvézère watershed contains apple production for agricultural diversification and the downstream portion of the Aixette watershed is in a peri-urban area. The agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…The timing and frequency of sampling, location and number of sampling sites, and the duration of monitoring are all important considerations [11,19,34]. The frequency of sampling and duration of monitoring should consider the dynamic range of pesticide concentration and variability over time to ensure that peak concentrations are not missed, and long-term trends are correctly interpreted [35]. Likewise, the timing of sampling should consider the hydrological system and the influence of events such as rainfall to peak concentrations [36][37][38].…”
Section: Design Of Monitoring Programmesmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing and frequency of sampling, location and number of sampling sites, and the duration of monitoring are all important considerations [11,19,34]. The frequency of sampling and duration of monitoring should consider the dynamic range of pesticide concentration and variability over time to ensure that peak concentrations are not missed, and long-term trends are correctly interpreted [35]. Likewise, the timing of sampling should consider the hydrological system and the influence of events such as rainfall to peak concentrations [36][37][38].…”
Section: Design Of Monitoring Programmesmentioning
confidence: 99%
“…Field applications including device performance has been extensively investigated in comparative studies assessing various PSDs [8,12,36,89,119], and other sampling methods [8,9,42,43,84,115] for pesticides in a range of aqueous matrices. Other field applications have focused on passive sampling within the context of regulatory monitoring [11,32,120], and to optimise strategies to characterise pesticide flux and identify analytes originating from episodic or continuous sources within passive sampling data [35,116]. A significant portion of the literature for each PSD concerns calibration and performance, including the influence of ambient conditions on uptake [103,108,121].…”
Section: Applications Of Passive Sampling For Polar Pesticidesmentioning
confidence: 99%
“…Challis et al (2018), also in Canada (Red River -Lake Winnipeg), showed that using POCIS was possible to estimate the main sources of pesticides (i.e., atrazine from the United States and neonicotinoid both from Canadian and the United States agriculture fields) and signaled the time-scale concerning application and detection in surface water. Guibal et al (2017), working in headwaters in two small catchments in France, aware to difficulty for monitoring the pesticides frequency and concentration fluctuation using active or passive sampling. They identified the three possible types of behavior (active >, = and < POCIS) when compared grab and passive sampling in relation to pesticides concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Quality assurance and control were used to control all deviations arising during analysis. The details of this analytical procedure were previously given and are described in the Supplemental Data of Guibal et al (2015a, 2018b).…”
Section: Methodsmentioning
confidence: 99%